2018
DOI: 10.1016/j.ijsu.2018.03.054
|View full text |Cite
|
Sign up to set email alerts
|

Pancreaticoduodenectomy is justified in a subset of elderly patients with pancreatic ductal adenocarcinoma: A population-based retrospective cohort study of 4,283 patients

Abstract: Advanced age (age ≥75 years) is not an independent risk factor for DSS. PD is justified in a subset of elderly PDAC patients; however, it should be performed in a high-volume center to minimize the risk of post operative complications. Future studies should explore individualized treatment strategies for elderly patients with undifferentiated tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…13,15 Other series reported that advanced age, comorbidity, body mass index (BMI), tumor markers, resection margin, and adjuvant therapy are also predictors of outcome in PDAC. [15][16][17] Tumor markers like CA19-9 may be elevated in more than 80% of the patients with PDAC, it is usually used as a predictor marker of tumor recurrence after resection and very high levels can be used for diagnosis especially if it was used with elevated carcinoembryonic antigen (CEA). Hartwig et al showed that elevated CA19-9 >400u/ml is a strong predictor of low survival, as seen in our study, but cholestasis can affect the level of CA19-9 and CEA as it is excreted in bile.…”
Section: Discussionmentioning
confidence: 99%
“…13,15 Other series reported that advanced age, comorbidity, body mass index (BMI), tumor markers, resection margin, and adjuvant therapy are also predictors of outcome in PDAC. [15][16][17] Tumor markers like CA19-9 may be elevated in more than 80% of the patients with PDAC, it is usually used as a predictor marker of tumor recurrence after resection and very high levels can be used for diagnosis especially if it was used with elevated carcinoembryonic antigen (CEA). Hartwig et al showed that elevated CA19-9 >400u/ml is a strong predictor of low survival, as seen in our study, but cholestasis can affect the level of CA19-9 and CEA as it is excreted in bile.…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective analyses have evaluated the value of adjuvant chemotherapy in the subset of elderly patients. The latest retrospective cohort research led by Mehtsun et al has found that receipt of adjuvant chemotherapy Hilal et al [51] Retrospective 524 Young: 64 ( Lu et al [52] Retrospective 4283 Young: 64 ( Wu et al [53] Retrospective Satoi et al [55] Retrospective 556 ≥80 2007-2014 Pancreatectomy vs chemotherapy, palliative therapy OS 22.8 vs 18.5 0.64 (0.44-0.93) .020…”
Section: Safety Feasibility and Effect Of Chemotherapy In Elderly Pda...mentioning
confidence: 99%
“…However, it was uncertain whether surgery will benefit the elderly patients. Some researchers suggested that the prognosis in the elderly was poorer than in the younger patients ( 8 , 9 ), while others hold the opposed points of view ( 10 12 ). What seems clear, though, is that the incidence of postoperative complications is much higher in the elderly patients ( 13 16 ).…”
Section: Introductionmentioning
confidence: 99%